Patient experiences with hypertrophic cardiomyopathy: a conceptual model of symptoms and impacts on quality of life - Erica Zaiser; Amy J. Sehnert; Ashley Duenas; Sara Saberi; Ella Brookes; Matthew Reaney (SpringerOpen, 2020)
Abstract Background Hypertrophic cardiomyopathy (HCM) is a primary myocardial disorder defined by left ventricular hypertrophy that cannot be explained by another cardiac or systemic disease. There is a general lack of knowledge about patients' perspectives on the symptoms and day-to-day limitations they experience as a result of HCM. We therefore sought an in-depth understanding of patients' experiences of obstructive (oHCM) and nonobstructive (nHCM) forms of the disease, including symptoms and their quality of life impacts, and to develop a conceptual model to capture them. Methods Development of the HCM conceptual model involved a web-based survey to capture patients' insights, a targeted literature review (which included relevant guidelines and patient advocacy websites), one-to-one interviews with clinical experts, and one-to-one qualitative concept elicitation interviews with patients. Key symptoms and their impacts most important to patients' experiences were identified and used to develop a conceptual model of the patient experience with HCM. Results The HCM symptoms reported by patient interviewees (n = 27) were largely consistent with findings from the patient web survey (n = 444), literature review, and interviews with three expert clinicians. The symptoms most commonly reported in patient interviews included tiredness (89%), shortness of breath (89%), shortness of breath with physical activity (89%), and dizziness/light-headedness (89%). Other symptoms commonly reported included chest pain (angina) (70%), chest pain (angina) with physical exertion (70%), and palpitations (fluttering or rapid heartbeat) (81%). The most commonly reported impacts of HCM symptoms on patients' lives included limitations to physical activities (78%), emotional impacts, including feeling anxious or depressed (78%), and impacts on work (63%). Symptoms and impacts were similar for both oHCM and nHCM. Conclusions A conceptual model was developed, which identifies the core symptoms that patients with oHCM and nHCM reported as most frequent and most important: shortness of breath, palpitations, fatigue/tiredness, dizziness/light-headedness, and chest pain, as well as the impacts those symptoms have on patients' lives. This HCM conceptual model reflecting patients' experiences and perspectives was used in the development of a patient-reported outcomes instrument for use in clinical trials and it may also help inform the clinical management of HCM.